Geoscience of Climate and Energy 8. Climate Models: Are They Compatible with Geological Constraints on Earth System Processes? - Peltier, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY Models of the global warming process are obliged to include many important small-scale processes that cannot be explicitly represented, given the low spatial and temporal resolution at which the models can be integrated. As the parameterizations of these processes, in terms of the resolved scale fields, must be tuned to permit them to enable the models to fit climate observations from the instrumental era, it is an issue as to whether such models remain robust when they are applied to the prediction of future warming trends. Geological inferences of past climate conditions provide a means by which the robustness of the models may be assessed. In this paper, two examples of such tests are described, both of which demonstrate that a state-of-the-art model is able to accurately simulate past conditions that differ radically from modern.